2017
DOI: 10.4236/jtr.2017.54026
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Hematologic Characteristics in Newly Diagnosed Pulmonary Tuberculosis Patients at Diagnosis in Kinshasa

Abstract: Context: The burden of TB in Africa tends to be exacerbated by the socio-economic situation and the high prevalence of intercurrent infections such as HIV, malaria and non-specific bacterial infections. These factors often result in anemia, making patients at high risk for anemia. Objective: We aimed to gain insights into the characteristics of anemia, hematologic variations and socio-economic status in untreated pulmonary TB patients (PTB) in Kinshasa, the Democratic Republic of Congo. Methods: We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
(49 reference statements)
2
11
0
1
Order By: Relevance
“…We found a prevalence of anemia similar to those observed in studies carried out in Asia [ 7 ] and Africa [ 5 , 11 , 13 , 15 , 23 ]. However, Lee et al showed a lower prevalence of anemia in South Korea (31.9%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found a prevalence of anemia similar to those observed in studies carried out in Asia [ 7 ] and Africa [ 5 , 11 , 13 , 15 , 23 ]. However, Lee et al showed a lower prevalence of anemia in South Korea (31.9%).…”
Section: Discussionsupporting
confidence: 89%
“…We observed that conditions predicting nutritional deficiency (such as low BMI, history of weight loss, and low albumin levels) were more frequent in anemic than in nonanemic patients, and C-reactive protein, a marker of an active inflammatory process, was significantly higher in patients with anemia. Other studies have also shown an association of anemia with hypoalbuminemia [ 17 , 23 ], increased C-reactive protein [ 7 , 17 , 23 ] and decreased BMI [ 8 , 15 , 16 ]. These observations, together with the evidence of decreased MCH and MCV in patients with anemia and the significant prevalence of microcytic hypochromic anemia (27.8% of anemia cases), allow us to speculate that important causes of anemia in TB patients may be iron nutritional deficiency and/or its decreased availability to erythropoiesis due to alterations of its metabolism in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, macrocytic anemia is often identified in less than 10% of patients at the time of diagnosis of TB 18 . Normocytic hypochromic picture is also reported in studies with a variable frequency, including 32.5% in Ethiopia 23 , 47.5% in the Democratic Republic of Congo 24 . It is noted that the observed variation might be associated to the impact of HIV/AIDS and the differences in the cutoff values used to define the morphological pattern of anemia.…”
Section: Introductionmentioning
confidence: 71%
“…16 Mulenga reported anemia in 69% of cases and it was moderate in 92% of cases; iron deficiency anemia was predominant type and he showed that hypoalbuminemia, alcohol intake and C-reactive protein (CRP) had an effect on anemia. 17 Kulkarni in 2017 also reported IDA as the predominant type and anemia was seen in 69.2% of cases and mostly it was mild. 18…”
Section: Discussionmentioning
confidence: 95%